2007
DOI: 10.1007/s00198-007-0510-1
|View full text |Cite
|
Sign up to set email alerts
|

Rate and circumstances of clinical vertebral fractures in older men

Abstract: Summary-We examined the rate of clinical vertebral fractures, and the circumstances associated with the fractures, in a cohort of 5,995 US older men. Fractures were more common in the most elderly men, and were usually associated with falls and other low-energy trauma.Introduction-Little is known about clinical vertebral fractures in older men. We postulated that clinical vertebral fractures occur with falls, affect men with osteoporosis, and are more common as age increases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
2
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(74 citation statements)
references
References 48 publications
2
67
2
3
Order By: Relevance
“…(21) However, the majority of studies have found lower mean BMI in vertebral fracture cases or no independent association with BMI for vertebral fracture. (22)(23)(24)(25)(26) The subclinical nature of most vertebral fractures and the difficulty of accurately measuring thoracic spine BMD by dual-energy X-ray absorptiometry (DXA) present particular challenges to the evaluation of adiposity and obesity on vertebral BMD and fracture risk.…”
Section: Introductionmentioning
confidence: 99%
“…(21) However, the majority of studies have found lower mean BMI in vertebral fracture cases or no independent association with BMI for vertebral fracture. (22)(23)(24)(25)(26) The subclinical nature of most vertebral fractures and the difficulty of accurately measuring thoracic spine BMD by dual-energy X-ray absorptiometry (DXA) present particular challenges to the evaluation of adiposity and obesity on vertebral BMD and fracture risk.…”
Section: Introductionmentioning
confidence: 99%
“…117 Assessment of bone density at 2-year intervals is advisable in hypogonadal men, and serum testosterone measurements should be obtained in all men with osteopenia. 118,119 Trials of the effects of testosterone replacement therapy on bone mineral density yielded mixed results. 120 Increases in spinal bone density have been realized in hypogonadal men, 121 with most treated men maintaining bone density above the fracture threshold.…”
Section: Bone Mineral Densitymentioning
confidence: 99%
“…Assessment of bone density at 2-year intervals is advisable in hypoLate-onset hypogonadism in males C Wang et al gonadal men and serum testosterone measurements should be obtained in all men with osteopenia. 49,50 Recommendation 7: testosterone and sexual function 7.1. The initial assessment of all men with ED and/ or diminished libido should include determination of serum testosterone.…”
Section: Recommendation 5: Body Compositionmentioning
confidence: 99%